Penggunaan Permainan Lompat Karet Sebagai Media Pembelajaran Motorik Anak Usia 5–6 Tahun - Rohayu Fadillah; Lydia Margaretha; Indri Maryanisah; Tiara.D.O.H. W; Oliviya Wulandari; Kendi Julia Narti; Elka Yulia Santera (Early Childhood Research and Practice, 2026)
This study aims to determine the use of the Lompat Karet game as a learning medium to improve the motor skills of children aged 5–6 years. This modern traditional game, typical of Central Bengkulu, has elements of movement that involve body coordination, balance, agility, and cooperation between children, making it a fun learning activity for early childhood. The research method used was descriptive qualitative, with children aged 5–6 years as subjects. Data collection techniques were conducted through observation, interviews, and documentation during the game activities. The results showed that the Lompat Karet game can improve children's gross motor skills, such as running, jumping maintaining balance, and coordinating body movements. Furthermore, this game also helps increase children's self-confidence, social interaction, and enthusiasm for learning. The use of traditional games as a learning medium provides a more active and enjoyable learning experience, making it easier for children to understand the activities presented by the teacher. Therefore, the lompat karet game can be used as an alternative learning medium for motor skills for early childhood and as an effort to preserve the traditional games of Central Bengkulu.